Schaum's outline of theory and problems of fourier analysis: with application to boundary value problems - Spiegel, Murray R (Tata McGraw-Hill, 2005)
Schaum's outline of theory and problems of fourier analysis: with application to boundary value problems / Spiegel, Murray R. -- New Delhi: Tata McGraw-Hill, 2005 515.2433 S755 No. of Copies : 1